2017
DOI: 10.1111/1759-7714.12541
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery using uniportal video‐assisted thoracic surgery for lung cancer: A preliminary study

Abstract: BackgroundThis study investigated the clinical efficiency of enhanced recovery after surgery (ERAS) using uniportal video‐assisted thoracoscopic surgery for lung cancer.MethodsThe clinical data of 83 patients with early‐stage non‐small cell lung cancer (NSCLC) at the First Affiliated Hospital of Soochow University from January 2016 to February 2017 were retrospectively analyzed. ERAS was applied to 38 patients (ERAS group), while 45 patients received conventional surgical treatment (control group). The operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 15 publications
(22 reference statements)
1
43
0
Order By: Relevance
“…In the study reported in 2018, patients in the ERAS group had better results on the third day after surgery than on the first day in the visual analog scale (VAS), whilst the length of hospital stay in the ERAS group was shorter than in the control group. The results are probably due to a beneficial aspect of the reduction in trauma caused by uniportal VATS (Table ).…”
Section: Uniportal Vatsmentioning
confidence: 99%
“…In the study reported in 2018, patients in the ERAS group had better results on the third day after surgery than on the first day in the visual analog scale (VAS), whilst the length of hospital stay in the ERAS group was shorter than in the control group. The results are probably due to a beneficial aspect of the reduction in trauma caused by uniportal VATS (Table ).…”
Section: Uniportal Vatsmentioning
confidence: 99%
“…Lung protective ventilation has become an integral part of protocols to prevent pulmonary complications like pneumonia or accelerate the recovery time [e.g., enhanced recovery after surgery (ERAS)], which is both also, wanted in LVR (23)(24)(25).…”
Section: Lung Protective Ventilationmentioning
confidence: 99%
“…Strong evidence exists for a normovolemic fluid regimen in thoracic surgery ( Table 2). Balanced crystalloids are recommended, saline solutions should be avoided and colloids should only be used as a substitute for blood loss (23,25).…”
Section: Perioperative Fluid Managementmentioning
confidence: 99%
“…Nowadays, radical surgery is regarded not only as the optimal therapeutic option for early‐stage non‐small‐cell lung cancer (NSCLC), but also as the cornerstone of multidisciplinary treatments for more advanced NSCLC . Since the 1990s, single lobectomy via video‐assisted thoracoscopic surgery (VATS), a minimally invasive procedure providing access to the chest cavity, has been developed as a modern surgical modality for operable NSCLC, offering more advantages than conventional thoracotomy in terms of the cosmetic wounds, pain and stress control, preservation of pulmonary function, and enhanced recovery . Despite advances in surgical techniques and perioperative care, however, the morbidity rate after VATS lobectomy remains 26.2–36.3% …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Since the 1990s, single lobectomy via video-assisted thoracoscopic surgery (VATS), a minimally invasive procedure providing access to the chest cavity, has been developed as a modern surgical modality for operable NSCLC, offering more advantages than conventional thoracotomy in terms of the cosmetic wounds, pain and stress control, preservation of pulmonary function, and enhanced recovery. 6,[8][9][10][11][12] Despite advances in surgical techniques and perioperative care, however, the morbidity rate after VATS lobectomy remains 26.2-36.3%. 6,[11][12][13] As a fatal complication following elective pulmonary resection, the postoperative management of chylothorax (which is generally secondary to thoracic duct injury, with its tributaries), poses a great challenge to thoracic surgeons because of the uncontrollable accumulation of fatty lymphatic fluid in the pleural space and subsequently high mortality, up to 30%.…”
Section: Introduction Rationalementioning
confidence: 99%